1986
DOI: 10.1111/j.1365-2885.1986.tb00063.x
|View full text |Cite
|
Sign up to set email alerts
|

The lack of effect of inoculation with equine influenza vaccine on theophylline pharmacokinetics in the horse

Abstract: Several studies conducted during the past few years have shown that the pharmacokinetics of a variety of drugs may be altered following viral infection or vaccination. The elimination of drugs which are extensively metabolized, such as theophylline, may be prolonged, especially following exposure to RNA viruses such as Type A influenza or similar orthomyxoviruses. The purpose of this study was to determine whether vaccination of horses with equine influenza virus affected pharmacokinetic parameters describing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…This value agrees with some previous reports (Errecalde et al, 1984;Ingvast Larson et al, 1985), although a faster elimination rate was reported by Short et al (1986).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This value agrees with some previous reports (Errecalde et al, 1984;Ingvast Larson et al, 1985), although a faster elimination rate was reported by Short et al (1986).…”
Section: Discussionsupporting
confidence: 94%
“…However, values smaller than ours (mean 298 ml) were found by Short et al (1986). The mean apparent volume of distribution (Va) of 1.35 L/kg indicates extensive distribution to the extravascular tissues.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…The possibility of an interaction was therefore suspected and reported in cases in which signs and symptoms of carbamazepine toxicity were observed a few days after immunization [69]. Vaccination has also been reported to influence serum concentrations of other drugs including theophylline [70][71][72][73][74][75], chlordiazepoxide, phenytoin, phenobarbital, and lorazepam [16].…”
Section: Discussionmentioning
confidence: 99%